Viral Retinitis following Intraocular or Periocular Corticosteroid Administration: A Case Series and Comprehensive Review of the Literature - Takakura, Ako (2014)
PURPOSE: To describe viral retinitis following intravitreal and periocular corticosteroid administration. METHODS: Retrospective case series and comprehensive literature review. RESULTS: We analyzed 5 unreported and 25 previously published cases of viral retinitis following local corticosteroid administration. Causes of retinitis included 23 CMV (76.7%), 5 HSV (16.7%), and 1 each VZV and unspecified (3.3%). Two of 22 tested patients (9.1%) were HIV positive. Twenty-one of 30 (70.0%) cases followed one or more intravitreal injections of triamcinolone acetonide (TA), 4 (13.3%) after one or more posterior sub-Tenon injections of TA, 3 (10.0%) after placement of a 0.59-mg fluocinolone acetonide implant (Retisert), and 1 (3.3%) each after an anterior subconjunctival injection of TA (together with IVTA), an anterior chamber injection, and an anterior sub-Tenon injection. Mean time from most recent corticosteroid administration to development of retinitis was 4.2 months (median 3.8; range 0.25–13.0). Twelve patients (40.0%) had type II diabetes mellitus. Treatments used included systemic antiviral agents (26/30, 86.7%), intravitreal antiviral injections (20/30, 66.7%), and ganciclovir intravitreal implants (4/30, 13.3%). CONCLUSIONS: Viral retinitis may develop or reactivate following intraocular or periocular corticosteroid administration. Average time to development of retinitis was 4 months, and CMV was the most frequently observed agent. Diabetes was a frequent co-morbidity and several patients with uveitis who developed retinitis were also receiving systemic immunosuppressive therapy.